Estudo comparativo da sinterização em forno convencional e por microondas nas propriedades não ôhmicas do composto cerâmico CaCu3Ti4O12 / CaTiO3 com adição de SnO2 - Peinado, Gabriel Cotrim de Cesare [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In this work, CaCu3Ti4O12 / CaTiO3 ceramics added with 1%, 2% and 5% of SnO2 were synthesized by solid state reaction. After determining the ideal calcination temperature for each sample, all samples were calcined at the same temperature guaranteeing the formation of the phases and allowing comparative study to be conducted among all the ceramic compositions. After the calcination process, the samples were characterized regarding its structure (X-ray diffraction) and microstructure (scanning electron microscopy) in order to determine the phases present in the material, as well as its morphological characteristics. Once the analysis of the powdered ceramics were done, we proceeded to the uniaxial pressing studies, aiming to obtain the stress that maximized the green density of the ceramics in the form of bulk. After obtaining the ceramics in bulk form, the sintering temperature was determined by the dilatometry technique and sintering studies in a conventional oven. With the sintered ceramics in the best condition (1100 ºC, for 2 h.), physical (Archimedes method), structural (XRD and Rietveld-Toraya refinement), microstructural (SEM) and electrically (E vs. J and Nyquist diagrams to determine , Er, if and tan) the pure and tin oxide-enhanced CCTO/CTO based samples. The structural characterization of the sintered ceramics conventionally indicated the presence of two phases in the system, being these CTO and CCTO, in amounts previously reported in the literature (67% and 33%, respectively). From the microstructural point of view, it was noticed that the ceramic grains decreased as the percentages of SnO2 added increased, which directly reflects on the varistor property of the ceramics, since the lower leakage current (if = 0.735 mA) was determined for the composition of 2% SnO2, which had one of the smallest grain sizes ... (Complete abstract click electronic access below)

Neste trabalho, cerâmicas à base de CaCu3Ti4O12/CaTiO3 acrescidas de 1%, 2% e 5% de SnO2 foram sintetizadas pelo método de reação em estado sólido. A temperatura de calcinação ideal foi determinada através de análises termogravimétricas, de forma que todas as amostras foram calcinadas a uma mesma temperatura que garantisse a formação das fases e que pudesse ser analisada de forma correlativa entre todas as composições cerâmicas. Posteriormente à calcinação dos pós-cerâmicos, realizaram-se as caracterizações estruturais (difratometria de raios X) e microestruturais (microscopia eletrônica de varredura), a partir das quais foi possível determinar as fases presentes no material, bem como suas características morfológicas. Feitas as análises das cerâmicas em pó, partiu-se para os estudos de prensagem uniaxial de efeito simples, visando à maximização da densidade a verde das cerâmicas na forma de bulk. Tendo se obtido as cerâmicas na forma de bulk, determinou-se a temperatura de sinterização adequada aos corpos cerâmicos, através da técnica de dilatometria e de estudos de sinterização em forno convencional. Com as cerâmicas sinterizadas na melhor condição (1100ºC, por 2 h.), caracterizaram-se física (método de Arquimedes), estrutural (DRX e refinamento Rietveld-Toraya), microestrutural (MEV) e eletricamente (construção das curvas E vs. J e de Nyquist para determinação de , Er, if e tan) as amostras à base de CCTO/CTO puras e acrescidas de óxido de estanho. A caracterização estrutural das cerâmicas sinterizadas convencionalmente indicou a presença de duas fases no sistema, sendo estas o CTO e o CCTO, em quantidades previamente reportadas na literatura (67% e 33%, respectivamente). Do ponto de vista microestrutural, percebeu-se que os grãos das cerâmicas diminuíram à ... (Resumo completo, clicar endereço eletrônico abaixo)
Comparative study of sintering in conventional and microwave oven on the non-ohmic properties of the CaCu3Ti4O12 / CaTiO3 ceramic compound with addition of SnO2
Keywords: Varistores; Sinterização; Ceramica (Tecnologia); Sintering